Роль непрерывного образования в ПОДГОТОВКе НАУЧНО-ПЕДАГОГИЧЕСКИХ КАДРОВ В современных условиях ВУЗа республики узбекистан - Рахимов, Б. (SCIENCE and SOCIETY, 2020)
Given article is written about the system of constraint education in Uzbekistan on the basis of “National program of training personnel”, and also special attention is paid to the system of reforming education. This article discusses the modernization process of the preparation of the teaching staff (highly qualified scientific-pedagogical personnel) in Uzbekistan, substantiates the reasons for the increasing role of highly qualified specialists at the present stage of development of science and education, draws the conclusion about the need for changes in the preparation of the scientific-pedagogical teaching staff.